P99 Renal and bone safety of tenofovir alafenamide vs tenofovir disoproxil fumarate. (18th May 2015) - Post, Frank; Sax, Paul; Saag, Michael; Yin, Michael; Oka, Shinichi; Koenig, Ellen; Trottier, Benoit; Andrade, Jaime; Cao, Huyen; Fordyce, Marshall
Abstract : Background: Off-target renal and bone side effects may occur with tenofovir disoproxil fumarate (TDF) use. Compared with TDF, tenofovir alafenamide (TAF) results in significantly reduced plasma tenofovir (TFV) and may have less renal and bone toxicity. Methods: Treatment naïve HIV-1+ adults were randomised 1:1 to a single tablet regimen of E/C/F/TAF or E/C/F/TDF once daily in two double blind studies. Assessments for all subjects included measures of glomerular and proximal renal tubular function, and bone mineral density (BMD). Four pre-specified secondary safety endpoints were tested: serum creatinine, treatment-emergent proteinuria, spine and hip BMD. Week 48 off-target side effects data are described. Results: 1, 733 subjects were randomised and treated. Plasma TFV was >90% lower (mean AUCtau 297 vs. 3, 410 ng·hr/mL) in the E/C/F/TAF arm, compared to the E/C/F/TDF arm. Serum creatinine (mean change: +0.08 vs +0.11 mg/dL, p < 0.001), quantified proteinuria (UPCR, median % change; -3 vs +20, p < 0.001), and fractional excretion of phosphate (median % change; +0.9 vs +1.7), all favoured E/C/F/TAF. There were no cases of proximal tubulopathy in either arm. Mean% decrease in BMD was significantly less in the E/C/F/TAF arm for both lumbar spine (−1.30 vs −2.86, p < 0.001) and total hip (−0.66 vs −2.95, p < 0.001). Conclusions: Through 48 weeks, subjects receiving E/C/F/TAF had significantly better outcomes related to renal and bone health than those treated with E/C/F/TDF;. These data demonstrate important safety benefits of TAF relative to TDF, especially given the ageing of the HIV population and the need for long-term treatment.